Modeling acquaintance networks based on balance theory - Vukašinović, Vida; Šilc, Jurij; Škrekovski, Riste (Zielona Góra: Uniwersytet Zielonogórski)
An acquaintance network is a social structure made up of a set of actors and the ties between them. These ties change dynamically as a consequence of incessant interactions between the actors. In this paper we introduce a social network model called the Interaction-Based (IB) model that involves well-known sociological principles.
Keywords: social networks; small world; balance theory; pheromone infrastructure